ANALYSIS OF THE EFFECT OF SUNLIGHT INTENSITY AND CONIDIUM DENSITY ON EDAMAME RUST DISEASE (PHAKOPSORA PACHYRHIZI) IN IMMATURE OIL PALM AREAS - Kevin Angelanta; Guntoro; Nurliana (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of sunlight intensity and conidium density on the intensity of leaf rust disease caused by Phakopsora pachyrhizi in edamame plants grown in immature oil palm areas. The study used a quantitative descriptive approach by observing sunlight intensity, conidium density, and disease intensity. The data were analyzed using multiple linear regression with SPSS after log transformation of the disease intensity variable to meet the normality assumption. The Kolmogorov-Smirnov test showed an Asymp. Sig. value of 0.200, indicating that the data were normally distributed. The model also showed no multicollinearity, as indicated by a Tolerance value of 0.904 and a VIF of 1.106, and no heteroscedasticity pattern was found in the residual scatterplot. The regression produced the equation Y = 0.830 + 0.000000039X1 + 0.033X2. Sunlight intensity did not have a significant partial effect, whereas conidium density had a positive and significant effect on disease intensity. Simultaneously, both variables had a significant effect, with an F-statistic of 440.049 and an R Square value of 0.954.